Responsibilities Of The Corporate Director Against The Dark Criminal Action In The Position Based On The Decision Of The Court Sumber Of Cirebon Regency (Studies on Decision No.202 / Pid.B / 2019 / PN.Sbr) - Junaidi Junaidi; Sri Endah Wahyuningsih; Ira Alia Maerani (Jurnal Daulat Hukum, 2020)
The problems of this study were 1) corporate position as the subject of criminal law in Indonesia? 2) law enforcement against corporations as subjects of a criminal offense of embezzlement in office at the Court Sumber of Cirebon Regency? 3) accountability of corporate directors to the crime of embezzlement in office by Court Sumber of Cirebon Regency.The method used by researchers is sociological approach juridical law and specification in this study were included descriptive analysis. The source and types of data in this study are primary data obtained from interviews with field studies The defendant and the Legal Counsel in prisons Cirebon, And secondary data obtained from the study of literature. Data were analyzed qualitatively.Based on the results of this study are The position of the corporation as a subject of criminal law in particular is currently only recognized in the Act governing the criminal offense outside the Criminal Code. Law enforcement has inkracht / final until a court decision with the principle of lex generalis / delict general, instead of using the principle of lex sepesialis for in the Penal Code there is no article regulating the criminal offense of corporate (Company Law) Law Company Limited of the Republic of Indonesia No. 40 of 2007 . Accountability director of the corporation against the crime of embezzlement in a position based on the decision of the Court Sumber of Cirebon Regency is from the start (LP) Police Report Number: LP B / 446 / X / 2017 / Jabar / RES CRB dated October 8, 2018 and has been decided by the Court in decision Number 202 / Pid.B / 2019 / PN Sbr.Keywords : Responsibility; Corporate; Crime; Fraud; Position.